Motoric Clinical Symptoms in Late Onset Parkinsonâs Disease at Dr. Hasan Sadikin General Hospital Bandung - Sivakurunathan, Jasvinee; Syamsudin, Thamrin; Tansah, Haryono (Althea Medical Journal, 2017)
Background: Parkinsonâs disease (PD) is a progressive neurological that disorder is characterized by a number of motoric symptoms which are resting tremor, bradykinesia, rigidity and postural disturbance. The main aim in carrying out this study was to observe the motoric clinical pattern in patients with late onset Parkinsonâs disease based on age, gender, and staging of the disease.Methods: This was a descriptive retrospective study to 89 medical record of patients with late onset Parkinsonâs disease from Neurology outpatient clinic of Dr. Hasan Sadikin General Hospital Bandung in the period January 2010 to January 2013. Total sampling was used to determine the population sample size The motoric clinical symptoms in patients with late onset Parkinsonâs disease were classified based on age at diagnosis, gender, and staging of the disease conducted using descriptive retrospective method. Besides, staging was made based on Hoehn and Yarl scale.Results: Overall, 92% of the patients with late onset Parkinsonâs disease had resting tremor, and postural instability was less frequently found in 21% of patients. Sixty one men suffered from this disease, 43% were from the age group 60â69, and 32% were in stage III.Conclusions: A majority of patients with the late onset Parkinsonâs disease show resting tremor that has the common motoric clinical pattern, followed by bradykinesia, rigidity, and some show postural instability. [AMJ.2017;4(1):11â5]DOI:Â 10.15850/amj.v4n1.1013